Global practices related to handling of faeces and urine in hospitals - results of an IFIC survey - Popp, Walter; Zorigt, Khand; Borg, Michael; Zerafa, Simeone; Khamis, Nagwa; Damani, Nizam; Sowande, Abimbola; Friedman, Candice; Goldman, Carol; Lieske, Tim; Lee, Terrie; Richards, Judith (International Journal of Infection Control, 2015)
In 2012 and 2013, IFIC board launched a survey about handling of faeces and urine in hospitals, available in 8 languages. There were 1.440 answers from 93 countries worldwide, 75% from urban hospitals. Answers were given for typical situation of defecation of patients, hand washing facilities, cleaning of defecation area, handling of defecation in bed, use and disinfection of bedpans. Also a lot of free comments were given. The results show a big influence of history, culture and religion. Before making recommendations, more knowledge should be known about this issue on a worldwide level.